Alexithymia, Depression, Inflammation, and Pain in Patients With Rheumatoid Arthritis. Issue 5 (May 2014) - Kojima, Masayo; Kojima, Toshihisa; Suzuki, Sadao; Takahashi, Nobunori; Funahashi, Koji; Kato, Daizo; Hanabayashi, Masahiro; Hirabara, Shinya; Asai, Shuji; Ishiguro, Naoki
<x xml:space="preserve">Abstract</x> Objective We previously reported that depression and inflammation have independent effects on pain severity in patients with rheumatoid arthritis (RA). Alexithymia is a personality trait characterized by deficits in cognitive processing and regulation of emotions. A broad association between alexithymia and various health problems has been suggested, including depression, inflammation, and pain. The objective of this study was to examine the independent influence of alexithymia on pain perception and its relationship to depression and inflammation. Methods We evaluated 213 RA outpatients who completed self‐administered questionnaires, including the Beck Depression Inventory‐II (BDI‐II) to measure depression severity, the 20‐item Toronto Alexithymia Scale (TAS‐20) to measure degree of alexithymia, and a visual analog scale to quantify perceived pain. Serum C‐reactive protein (CRP) levels were measured to quantify inflammation severity. Results An initial significant positive association between the TAS‐20 score and pain severity (P = 0.01) lost significance after controlling for BDI‐II score and CRP level using regression analysis. An interaction was observed among alexithymia, depression, and inflammation with regard to perceived pain. Among those without alexithymia, pain severity increased linearly with the CRP tertile levels regardless of the presence of depression (P < 0.001 for trend). No linear association between pain severity and CRP level was observed among those with alexithymia. Moreover, depressed patients with alexithymia (BDI‐II score ≥14 and TAS‐20 score ≥61) reported severe pain even at low CRP levels. Conclusion Alexithymia might have a substantial role in pain perception as well as depression in patients with RA. A biopsychosocial approach is essential to achieve better pain control.